An inspection of pipe by snake robot. (13th October 2016) - Trebuňa, František; Virgala, Ivan; Pástor, Miroslav; Lipták, Tomáš; Miková, Ľubica
The article deals with development and application of snake robot for inspection pipes. The first step involves the introduction of a design of mechanical and electrical parts of the snake robot. Next, the analysis of the robot locomotion is introduced. For the curved pipe, potential field method is used. By this method, the system is able to generate path for the head and rear robot, linking the environment with obstacles, which are represented by the walls of the pipe. Subsequently, the solution of potential field method is used in inverse kinematic model, which respects tasks as obstacle avoidance, joint limit avoidance, and singularity avoidance. Mentioned approach is then tested on snake robot in provisional pipe with rectangular cross section. For this research, software Matlab (2013b) is used as the control system in cooperation with the control system of robot, which is based on microcontrollers. By experiments, it is shown that designed robot is able to pass through straight and also curved pipe.